2020
DOI: 10.1002/rcm.8883
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive activities and chemical profile characterization using paper spray mass spectrometry of extracts of Eriobotrya japonica Lindl. leaves

Abstract: Rationale The loquat (Eriobotrya japonica Lindl.) is a fruit tree that has been used in Chinese medicine for thousands of years for the treatment of various diseases. The loquat leaf extracts contain several bioactive compounds with antioxidant and antimicrobial properties, and identification of these substances using quick and simple methods has been an analytical trend. Methods The influence of dehydration of loquat leaves (without drying, at 40°C, and at 60°C), the type of solvent (ethanol and methanol), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…As such, another aspect of our research was to verify the presence of phenolic compounds, especially flavonoids and phenylpropanoids, since these compounds are known for their antioxidant, antimicrobial, anti-inflammatory, and antiviral activity [ 5 , 6 , 7 ]. Other bioactive properties include modulation of vascular homeostasis, as well as antidiabetic, anti-obesity, and anticancer effects [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, another aspect of our research was to verify the presence of phenolic compounds, especially flavonoids and phenylpropanoids, since these compounds are known for their antioxidant, antimicrobial, anti-inflammatory, and antiviral activity [ 5 , 6 , 7 ]. Other bioactive properties include modulation of vascular homeostasis, as well as antidiabetic, anti-obesity, and anticancer effects [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paper spray mass spectrometry (PSMS) was applied to identify the natural products present in the ethanol extracts. This quick and efficient technique for chemical profile determination is commonly used in the clinic and in forensic research to identify specific ions through direct sample analysis [ 36 , 37 , 38 , 39 ]. This study showed no difference in the chemical profile of peel and seed samples.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses were performed in triplicate in positive and negative ionization modes. For PSMS analyses, a 2 µL sample volume and 40 µL of methanol were added to a triangular chromatographic paper (equilateral, 1.5 cm lengthwise) positioned 10 mm away from the mass spectrometer inlet [ 37 , 38 , 39 ]. A high voltage was then applied to the paper held by a copper clamp and attached to a three-dimensional moving platform for data acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] The list of phenolic compounds and triterpenes in loquat parts is extensive and includes hydroxycinnamic acid derivatives such as chlorogenic acid, neochlorogenic acid, methyl-chlorogenic acid, feruloylquinic acid, caffeoylquinic acid, hydroxybenzoic acid, ferulic acid, and caffeic acids as well as 3-p-coumaroylquinic acid, quercetin-3-O-galactoside, quercetin-3-O-glucoside, quercetin-3-o-rhamnoside, oleanolic acids, d-oleanolic acid, ursolic acid, hydroxyursolic acid, gallic acid, caffeic acid, ellagic acid, and catechin. 1,9,10 Owing to the antioxidant potential of bioactive compounds of loquat, 10,11 and the suggestion of their use as an alternative treatment for obesity, 12 we hypothesized that the use of E. japonica seeds, leaves, and fruits extract is beneficial in the treatment of obesity and hyperlipidemia. To the best of our knowledge, no thorough examination has explored this potential.…”
Section: Introductionmentioning
confidence: 99%